Dye sensitised solar power generating window: Towards environmentally sustainable energy efficiency in ICT - Umrani, Z.A. (Inderscience Publishers, 2021)
ICT equipment generates significant amount of green house gases. Presently, the ICT produces more than 830 million tons of CO2, that is about 2 of global CO2 emissions, and it is expected to double by 2020 (Chan et al., 2012; Pothitou et al., 2017; Park, 2018). There is a need for ICT to standardise, energy consumption and emissions and investigate means to reduce energy consumption. The electricity consumption which dominates direct carbon footprint of the ICT sector can be reduced by using renewable energy sources. The dye-sensitised-solar-cell (DSC) is a renewable energy device that works well inside a built-environment. The transparent characteristic of DSCs makes it suitable for building-integrated-photovoltaic (BIPV) applications such as windows. In this study, we successfully fabricated and assembled a transparent DSC which was used to power ICT products. Such building-integrated DSC systems can potentially power ICT devices in homes and offices. Copyright Â© 2021 Inderscience Enterprises Ltd.